2015
DOI: 10.1007/s11606-015-3280-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Racial Differences of Non-Small Cell Lung Cancer in the United States Military

Abstract: Differences by patient and disease characteristics were compared using Chi-square and ttest. Kaplan Meier curves and Cox proportional hazards regression assessed overall survival. RESULTS: The mean age at diagnosis was 66 years, 64 % were male, 72 % were Caucasian, 41 % were diagnosed at early stage, 77 % received treatment and 82 % had a history of tobacco use. Mean age at diagnosis was highest among Caucasians (67 years) and lowest among African Americans (AA; 62 years). Asian/Pacific Islanders (PI) were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Regarding cancer treatment, with the exception of dementia patients who received less treatment which was largely driven by less surgery, there was no overall difference between those with and without a mental health disorder. The lower likelihood of having unknown stage and the absence of differences in receiving cancer treatments may be attributed to a high accessibility to health care for beneficiaries in MHS, in which there are no or minimum cost barriers to laboratory tests, radiology workup, and cancer prevention and surveillance services (55). Moreover, in early 2000, the MHS launched the initiative of integration behavioral health services into primary care services (56), which have facilitated the care and follow up of beneficiaries with mental health disorders in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cancer treatment, with the exception of dementia patients who received less treatment which was largely driven by less surgery, there was no overall difference between those with and without a mental health disorder. The lower likelihood of having unknown stage and the absence of differences in receiving cancer treatments may be attributed to a high accessibility to health care for beneficiaries in MHS, in which there are no or minimum cost barriers to laboratory tests, radiology workup, and cancer prevention and surveillance services (55). Moreover, in early 2000, the MHS launched the initiative of integration behavioral health services into primary care services (56), which have facilitated the care and follow up of beneficiaries with mental health disorders in the system.…”
Section: Discussionmentioning
confidence: 99%
“…16,27 We observed no racial differences in survival among the entire cohort, which is similar to the findings of other studies evaluating the correlation between race and overall survival adjusted for covariates in patients with early-stage lung cancer. 14,15,20,28,29 Given the lower percentage of black patients receiving an operation and greater proportion of blacks having other/no treatment, we would have expected disparately worse survival outcomes in black patients. Farjah et al reported a 14% black-white difference in resection among patients to whom an operation was recommended, but the mortality risk was similar for the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of factors potentially mediate the race-survival association, including histologic type, smoking, and comorbidities. Studies have reported racial differences in lung cancer histologic type, 28,31 which is strongly associated with smoking, 20,33 and common lung cancer comorbidities such as COPD. 34,35 Although we adjusted for these factors, which is often lacking in other studies, we could not account for details such as packyears, smoking duration, and severity of comorbidities, which are more relevant predictors of survival.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that equality of access to health care afforded by the MTFs may mitigate racial variations in diagnosis of lung cancer and disease outcomes. 7 Although this is a reasonable conclusion based on this retrospective database analysis, the authors also recognized a key limitation of their study, namely whether active military service members from racial/ethnic minorities are representative of the US population of racial/ethnic minorities in general. It is particularly important to note, given the data suggesting that among lung cancer patients nationally, only about 4 % are veterans who have served in the US Armed Forces.…”
mentioning
confidence: 78%